Effects of Corporate Correspondence, Remuneration, Job Competition on Enthusiasm For Work Study RSUD Sunan Kalijaga Demak Regency - Aditya Angger Wibowo (International Journal of Economics and Management Sciences, 2025)
The purpose of this study is to show how corporate correspondence, compensation, and job competition impact enthusiasm for work in a study at RSUD Sunan Kalijaga Demak Regency. This study involved 173 employees of RSUD Sunan Kalijaga Demak Regency, which consisted of 121 respondents selected based on certain criteria. The purposive sampling method was used for sampling. According to calculations carried out using the SPSS version 23.0 programme, correspondence, compensation, and job competition have a positive impact on employee enthusiasm for work at RSUD Sunan Kalijaga Demak Regency. Multiple testing showed that corporate correspondence, compensation, and job competition together had a significant impact on employee interest in job studies at RSUD Sunan Kalijaga Demak Regency.